GRID TIE INVERTER UNTUK PLTS ATAP DI INDONESIA: REVIEW STANDAR DAN INVERTER YANG COMPLIANCE DI PASAR DOMESTIK - Priajana, P.G.G.; Kumara, I.N.S.; Setiawan, I.N. (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p9, 2020)
The Government started a million solar rooftop movement to help accelerate Indonesia's renewable energy target in 2025. In effect of ministerial regulation 49/2018, household customers are able to install grid tie photovoltaic and export excess energy to PLN. Inverter is a complex and a vital component to the performance of grid tie photovoltaic systems, therefore inverter used must follow applicable standard. This article reviews the avaibility of inverters for solar rooftop in Indonesia. The purpose of this article is to know the avaibility of inverter and how they are seen from applicable standard. From this research produced inverter database consisted of 513 inverter models. Inverter database then analyzed seen from its manufacturing status, inverter power output capacity, THD output, efficiency, and price. This information is crucial in choosing quality inverter so rooftop photovoltaic would work effectively and sustainably. Presently various inverters with capacity 0,5 kW - 10 kW already available which is suitable for solar rooftop application. There are already plenty inverters with THD output <3% that conform with Indonesia’s standard but many also still have not listed their THD output. Inverter efficiency is already >95% and available with an average price of Rp3,435,380/kW. List of inverter models that conform standard and certification presented in a table which served as output of this research.